Community Structure of Coleoptera Families and Staphylinidae Species as Potential Bioindicators in Atlantic Rain Forest - Taise Cristina Plattau Arenhardt; Marcelo Diniz Vitorino; Sebastião Venâncio Martins (Floresta e Ambiente)
Abstract Beetles (Coleoptera) are structurally and functionally important in tropical forest ecosystems. The present research aimed to characterize Coleoptera families and Staphylinidae species in areas of native forest and pastures undergoing restoration with nucleation techniques in the Serra do Itajaí National Park. The collections were carried out from pitfall traps, from April/2017 to December/2018. A total of 2619 individuals of Coleoptera were collected, distributed in 30 families, and 637 individuals of Staphylinidae, distributed in 46 species. The abundance, richness, and composition of Coleoptera families and Staphylinidae species varied significantly between native forest and pasture with the inclusion of nucleation techniques for restoration. Microclimate had a significant influence on the ecological parameters analyzed. We identified families and species characteristic of forests and pastures. Less specific taxonomic identification levels showed significant differences, enabling its application as a potential bioindicator of restoration. Our results suggest that pasture areas still support an impoverished leaf litter beetle community.